Konsep Uang Menurut Islam dan Dampaknya pada Sustainable Development - Risma Kurniawan; Karina Dwi Tasari; Winda Putri Handayani; Eka Dima Agustrisna (Ekopedia: Jurnal Ilmiah Ekonomi, 2025)
This research aims to analyze the conceptual impact of money in Islam on achieving the Sustainable Development Goals (SDGs). Amidst the global crisis (economic, social, environmental), the SDGs agenda requires an ethical financial framework. This research argues that the fundamental philosophy of Islamic finance is not only the product that offers this foundation. Using the library research method with a descriptive-analytical approach, this study maps the impact of the Islamic money concept on the three pillars of the SDGs. The findings indicate that the Islamic money concept is inherently aligned with the SDGs: 1) The prohibition of usury impacts the economic pillar (SDG 8, 9), 2) The principles of anti-hoarding and ZISWAF impact the social pillar (SDG 1, 10), 3) The principles of Khalifah and anti-corruption impact the environmental pillar (SDG 12, 13). Although theoretically aligned, this research also highlights implementation challenges due to the gap between ideal theory and current Islamic financial industry practices.